Oral and periodontal features of autosomal recessive syndromes: a tabular review - Reddy, Sesha; Vandana, Kharidhi Laxman; Shetty, Shishir Ram (Brazilian Dental Science, 2019)
Objective: To systematically review the data and results of case reports of autosomal recessive syndromes associated with periodontitis. Material and Methods: An internet search using Google and PubMed search engine and keywords- autosomal recessive, periodontitis, syndromes, periodontium and gingiva was carried out. Full-text articles in the English language of all the case reports and reviews that were published in journals from the year 1966 to 2016 were obtained and evaluated and presented in tabular form. Abstracts and articles published in other languages were not included in the review. Results: The data available from the clinical trials were analyzed and presented under broad headings of, systemic features, dental features, periodontal features and laboratory findings presented in tabular form. Conclusion: Many autosomal recessive syndromes with dental component also present with changes or alteration in the periodontium thus stressing the fact that thorough periodontal examination is important during the medical evaluation of patients with syndromes Keywords Syndromes; Autosomal recessive; Periodontitis; Periodontium; Gingiva.